Penentuan Kinerja Usaha Kecil Menengah (UKM) Coffee Shop dengan Metode Data Envelopment Analysis (DEA) dan Comparative Performance Index (CPI) (Studi Kasus: 8 Coffee Shop di Meulaboh, Aceh Barat) - Arie Saputra; Muzakir Muzakir; Sofiyanurriyanti Sofiyanurriyanti; Fitriadi Fitriadi; Ida Nopiyanti (Universitas Teuku Umar, 2020)
This study discusses determining the performance of a coffee shop Small and Medium Enterprises (UKM) with the Data Envelopment Analysis (DEA) and Comparative Performance Index (CPI) method, determining performance is an important thing that must be done by a coffee shop UKM to win the competition with other coffee shop UKM. . The calculation of performance determination uses Data Envelopment Analysis (DEA), which is able to evaluate the relative efficiency level of a coffee shop unit, and which is non-parametric and multifactorial, both output and input. This study also uses the calculation of determining the performance of the Comparative Performance Index (CPI) as an alternative system in selecting coffee shop performance. This research was conducted at 8 coffee shop units in Meulaboh, West Aceh. This research was conducted to see the performance of the coffee shop which is still growing rapidly until now, considering that until now coffee shops are increasingly in demand by various groups. Attributes in determining performance are the number of customers, capital, income / profit, salary, number of workers and a questionnaire. From the results of the calculation of the Data Envelopment Analysis (DEA) all performance units are all efficiency because they get a value of 1 (100%) and in the Comparative Performance Index (CPI) calculation there are different rankings, namely warkop mae first rank, second rank arab coffee, third rank kupi atjeh ulee kareng, fourth in abudel's coffee and bistro, fifth in chaplin cafe & restaurant, sixth in gampong coffee shop and bistro, seventh in one cafe, and eighth in praja coffee.